2000
DOI: 10.1046/j.1365-2826.2000.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Clusters of Action Potentials can Increase or Decrease the Excitability of the Axons of Magnocellular Hypothalamic Neurosecretory Cells

Abstract: Extracellular recordings were made from supraoptic nucleus (SON) cells in urethane anaesthetized male rats in vivo. Two stimulating electrodes were positioned to activate the cells antidromically, one in the mid axon region of the cells and the other at the axon terminals. Trains of 5-20 just-subthreshold stimuli at 5 s intervals decreased the threshold for antidromic activation from both sites. Whereas neither single stimuli, nor the stimuli at the beginning of a train of 20 stimuli evoked antidromic action p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is not possible to measure transmitter release from the cells we recorded, but in the supraoptic nucleus the magnocellular neurones show greater efficiency in neuropeptide release for a given number of spikes with more patterned motifs of activity (Dutton & Dyball, 1979). It has also been known for some time that a brief series of short intervals can influence the excitability of some hypothalamic cells (Dyball & McKenzie, 2000) and we have recently shown that similar effects occur in cells of the suprachiasmatic nucleus (Dyball & Inyushkin, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…It is not possible to measure transmitter release from the cells we recorded, but in the supraoptic nucleus the magnocellular neurones show greater efficiency in neuropeptide release for a given number of spikes with more patterned motifs of activity (Dutton & Dyball, 1979). It has also been known for some time that a brief series of short intervals can influence the excitability of some hypothalamic cells (Dyball & McKenzie, 2000) and we have recently shown that similar effects occur in cells of the suprachiasmatic nucleus (Dyball & Inyushkin, 2005).…”
Section: Discussionmentioning
confidence: 69%
“…The terminals do not contain clearly separate pools of readily releasable and reserve vesicles, but rather a heterogeneous population differing in releasability ( 50 ). Other mechanisms also affect stimulus-secretion coupling, including changes in axonal excitability that result from activity-dependent changes in extracellular potassium concentration ( 51 , 52 ). In this study, our purpose was not to construct a detailed model of all of the mechanisms that contribute to stimulus-secretion coupling, but rather to produce a minimalist model that by matching available data on stimulus-secretion coupling would enable us to predict secretion from spiking activity ( 31 , 52–54 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the intervals between spikes and the variability and patterning of the inter‐spike interval sequence can profoundly affect the excitability of the axons of the neurosecretory cells (35, 36). The precise relationship between the information contained within a spike train and neurosecretory function, however, has not yet been established.…”
Section: Discussionmentioning
confidence: 99%